A Systematic Review of Women's Knowledge of Screening Mammography - Seaman, K.; Dzidic, Peta; Castell, E.; Saunders, C.; Breen, Lauren (Churchill Livingstone, 2018)
© 2018 Elsevier Ltd In light of the contention surrounding the benefit-to-harm ratio of screening mammography, this systematic review aimed to understand women's knowledge of screening mammography. The search yielded 35 studies of varying methodologies, published/completed between 1992 and 2017. Data was collected between November 2017 and February 2018 and utilised publications from member countries of the International Cancer Screening Network- Breast Cancer Division. Data was analysed using a narrative synthesis. The results of the review suggest that most women are aware of mammograms, however there was large variability regarding the awareness of false positives/negatives and about the purpose of screening. Some topics (e.g. radiation, commencement age) are well understood by women; however, others are not (e.g., cessation age, overdiagnosis, and mortality reduction). The findings need to be considered in light of the variability of methods used to assess women's knowledge and there is a need to develop psychometrically validated and culturally appropriate measures of knowledge regarding screening mammography. Further, the lack of consensus regarding what women ‘should’ know in order to provide informed consent has implications for understanding what informed consent in breast screening means in practice.